Streptococcus mutans-induced secondary caries adjacent to glass ionomer cement, composite resin and amalgam restorations in vitro Cárie secundária adjacente a restaurações de cimento de ionômero de vidro, resina composta e amálgama induzida por Streptococcus mutans in vitro - Adriana Gama-Teixeira; Maria Regina Lorenzeti Simionato; Silvia Nagib Elian; Maria Angela Pita Sobral; Maria Aparecida Alves de Cerqueira Luz (Brazilian Oral Research, 2007)
The aim of this study was to define, in vitro, the potential to inhibit secondary caries of restorative materials currently used in dental practice. Standard cavities were prepared on the buccal and lingual surfaces of fifty extracted human third molars. The teeth were randomly divided into five groups, each one restored with one of the following materials: glass ionomer cement (GIC); amalgam; light-cured composite resin; ion-releasing composite; and light-cured, fluoride-containing composite resin. The teeth were thermocycled, sterilized with gamma irradiation, exposed to a cariogenic challenge using a bacterial system using Streptococcus mutans, and then prepared for microscopic observation. The following parameters were measured in each lesion formed: extension, depth, and caries inhibition area. The outer lesions developed showed an intact surface layer and had a rectangular shape. Wall lesions were not observed inside the cavities. After Analysis of Variance and Component of Variance Models Analysis, it was observed that the GIC group had the smallest lesions and the greatest number of caries inhibition areas. The lesions developed around Amalgam and Ariston pHc restorations had an intermediate size and the largest lesions were observed around Z-100 and Heliomolar restorations. It may be concluded that the restorative materials GIC, amalgam and ion-releasing composites may reduce secondary caries formation. O objetivo deste estudo foi definir, in vitro, o potencial de materiais restauradores, usados rotineiramente na prática clínica, na inibição da cárie secundária. Cavidades padronizadas foram preparadas nas faces vestibulares e linguais de 50 terceiros molares humanos extraídos. Os dentes foram divididos aleatoriamente em 5 grupos, cada um restaurado com um dos seguintes materiais: cimento de ionômero de vidro (CIV); amálgama; resina composta fotopolimerizável; compósito que libera íons, e resina composta fotopolimerizável contendo flúor. Os dentes foram termociclados, esterilizados com radiação gama, expostos a um desafio cariogênico utilizando um sistema bacteriano com Streptococcus mutans e preparados para observação microscópica. Os parâmetros medidos em cada lesão formada foram: extensão, profundidade e área de inibição de cárie. As lesões externas formadas apresentaram camada superficial intacta e formato retangular. Não foram vistas lesões de parede no interior das cavidades. Após Análise de Variância e Análise de Componentes de Variância, foi observado que o grupo CIV apresentou as menores lesões e o maior número de áreas de inibição de cárie. As lesões formadas ao redor das restaurações de amálgama e Ariston pHc apresentaram tamanho intermediário e as maiores lesões foram observadas ao redor das restaurações dos grupos Z-100 e Heliomolar. Pode ser concluído que os materiais restauradores CIV, amálgama e compósitos que liberam íons podem reduzir a formação de cáries secundárias.